Using bespoke fluorescence microscopy to study the soft condensed matter of living cells at the single molecule level - Xue, Q; Harriman, O; Leake, M (2011)
The use of bespoke imaging tools and analysis can offer significant insight into the living counterpart of soft condensed matter. The soft matter of biological systems consists of molecular building blocks, a staple of which is protein. Protein molecules, so small that 1 billion would fit on the full-stop at the end of this sentence, carry out most of the vital activities in living cells. Many of these processes require the assembly of multiple proteins into remarkable biological machines. Obtaining the blueprints for the architecture of these machines is essential for understanding the workings of the cell. Here, we discuss recent biological physics experiments on functional single-celled organisms in which one can apply bespoke fluorescence microscopy imaging and analysis to monitor the number and dynamics of several different proteins at the nanometre length scale to a precision of single molecules. © Published under licence by IOP Publishing Ltd 2011.